2016
DOI: 10.1007/s10995-016-1986-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Background Television Exposure in Low-Income Mexican–American Preschoolers

Abstract: Objective Background television (TV) exposure is harmful to young children, yet few studies have focused on predictors of exposure. This study’s objectives were to elucidate demographic, environmental, and behavioral correlates of background TV exposure in low-income Mexican American preschoolers and to explore caregiver beliefs about the impact of such exposure. Methods A convenience sample of low-income Mexican American female primary caregivers of preschoolers (3–5 years old, n=309), recruited in safety-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
(40 reference statements)
1
8
0
2
Order By: Relevance
“…Given the limited literature on mobile media device use in relation to young children, studies on television screen time were also reviewed. Covariates included sex, 17 temperament, 18,19 non–mobile media use, 1 parent mobile media device use, 20,21 household income, 22 and parent education. 22…”
Section: Methodsmentioning
confidence: 99%
“…Given the limited literature on mobile media device use in relation to young children, studies on television screen time were also reviewed. Covariates included sex, 17 temperament, 18,19 non–mobile media use, 1 parent mobile media device use, 20,21 household income, 22 and parent education. 22…”
Section: Methodsmentioning
confidence: 99%
“…More detailed information on survey development and study procedures can be found in previously published articles. 19, 21…”
Section: Methodsmentioning
confidence: 99%
“…An array of family and home factors likely impact the use of TV in families with young children including ethnicity, family TV viewing habits, family socioeconomic status, and maternal depressive symptoms 21,22 . For example, even background TV exposure (i.e., while the caregiver is watching TV or during meals) is associated with poor outcomes in young children, including reduced parent–child interactions and lower reading levels 23 . The current study proposes and tests a conceptual model to explore conditions that are associated with excessive television viewing for children.…”
Section: Introductionmentioning
confidence: 99%